Кольцо Анубиса: роман / Владимир Клименко - Клименко Владимир Ильич (Clio-Dетектив, 2010)
Экземпляры: Ф20 (20211123) / Инвентарный номер: 62004 / Цена: 30.00 / Сис.шифр: Р2 / Авт.знак: К 49 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6